Experiential Tourism: Local Food Effect on How Tourists Experience Authenticity in Destiantion - Lame, Ahmad Aminu; Buba, Eldah Ephraim; Banu, Hyelni; Ibrahim, Sanusi (Researchparks Publishing, 2023)
Tourists leave their homes for destinations in search of new experience, they love to experience something they have never known or felt before. Many holiday makers do not put this into consideration while planning meals for tourists while in the destination. Some menus reflect what the tourists are used to eating at home offering nothing new in terms of food. The objectives of the study is to assess the acceptability of selected northern Nigeria delicacies by tourists coming to Bauchi as a destination and to examine the influence of tourists experience on local foods and whether achieving an authentic experience of local food is an important reason for visiting the destination. Survey method was used with two different types of questionnaires. The first questionnaire was used for the sensory evaluation of the six delicacies to be tasted. 250 tourists both domestic and international were used as taste panel group. The study reveals that local food experience is important to the tourists. Furthermore, the study finds out that authentic experience of local food is not enough reason for visiting the destination. The study therefore, recommends that, local food should be included in the menu of the tourists to enable them have memorable experience of the destinations identity which local food is one.